PENGARUH KONSENTRASI EKSTRAK ETANOL BONGGOL NANAS (Ananas comosus (L.) Merr) TERHADAP APOPTOSIS KARSINOMA SEL SKUAMOSA LIDAH MANUSIA - Fimma Naritasari; Hendri Susanto; Supriatno Supriatno (Majalah Obat Tradisional, 2010)
Squamous cell carcinoma is one of the most common malignancy in the oral cavity.  Currently, cancer treatment using surgery, radiotherapy, chemotherapy and its combination.  New strategy for cancer therapy is by searching herbal which can induce apoptosis. Bromelain is one of a potential anticancer agent that can induce apoptosis. Pineapple stem is one of a potential herbal medicine because of its bromelain enzyme content. The aim of this study was to investigate the relation between pineapple stem ethanol extract and apoptosis of oral tongue squamous cell carcinoma cell line. Oral tongue  squamous  cell  carcinoma  cell  line was  treated  with  three concentrations  under  IC50  of  pineapple  stem  ethanol  extract,  including  5.000, 5.500,  6.000  µg/ml.  In  apoptosis  test,  cell  stained  with  fluorochrome  ethidium bromide and acridine orange after 24 hours incubation. Fluorescence microscope was used for counting the cell. Viable cell would be stained green and apoptotic cell would be stained yellow to orange. Probit analysis was used to determine IC50 of pineapple stem ethanol extract on Oral tongue squamous cell carcinoma cell line. Pearson analysis used to know the correlation between pineapple stem ethanol extract concentration and Oral tongue squamous  cell  carcinoma  cell  line apoptosis. The  result  showed  that  there  was  a  positive  correlation  between concentration  of  pineapple  stem  ethanol extract  and  apoptotic  cell  (r=0,999, p<0,05). In conclusion, pineapple stem ethanol extract treatment induced apoptosis of  oral  tongue  squamous  cell  carcinoma  and  the  increases  of  pineapple  stem ethanol extract concentration followed by the increase of apoptosis induction.